MODERN LABORATORY DIAGNOSIS OF FOLIC ACID DEFICIENCY ANEMIA - Najmiddinova Nigora Kamoliddinovna; Uzokov Siroоiddin Sultonovich; Dusyorova Sokinabonu Aburazzoq kizi (TADQIQOTLAR.UZ, 2024)
Abstract:  Folic  acid  in  the  context  of  anemia  deficiency  is  becoming  an increasingly important topic in modern healthcare. Folic acid, being a water-soluble B vitamin,  plays  a  key  role  in  DNK  synthesis  and  the  formation  of  red  blood  cells. Deficiency of this vitamin leads to impaired performance of red blood cells, which, in turn,  causes  the  development  of  megaloblastic  anemia.  Folic  acid  is  especially important during pregnancy, as it is necessary for the development of the brain and spinal cord of babies. Getting enough folic acid during pregnancy can help prevent birth defects such as neural tube defects. Therefore, it is recommended that women planning pregnancy and pregnant women receive sufficient amounts of folic acid.